Teachers' Readiness and Ability in Designing Teaching Modules in The Independent Curriculum - Wiwit Sanjaya; Yeni ERITA; Rati Syafiana PUTRI; Novalina INDRIYANI (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
The curriculum continues to change and is developed according to the needs of the time. The purpose of curriculum development is to be able to facilitate all the needs of students so that the learning objectives are achieved optimally. The independent curriculum emerged as a renewal of the previous curriculum. One aspect that has changed is the teaching device in the form of teaching modules with many components in it. Therefore, most teachers experience difficulties in their preparation. The purpose of this study was to find out how the teacher's readiness and ability to develop teaching modules based on the Merdeka curriculum and steps that can be taken to improve the teacher's ability to develop teaching modules. Writing this article using a literature approach (literature review). The results of the study found that there were still many teachers who were not fully prepared to implement the independent learning curriculum, this could be seen from the fact that there were still many teachers who were unable and had difficulty in compiling teaching tools, one of which was the teaching module. Concrete efforts are needed to improve teacher abilities and competencies, including by holding training and or technical guidance related to the preparation of teaching devices according to the demands of the Merdeka curriculum. Thus, the problem of unpreparedness and the inability of teachers to compile teaching modules can be resolved properly.